Metaphors of rape culture in the female gothic: isolation and community - Thomason, Jannea (My University, 2017)
Scholars have struggled to define the Gothic as a cohesive genre. As a genre it defies restriction, though it does not loose it’s meaning as a category. In his introduction to The Oxford Book of Gothic Tales, Chris Baldick provides a unifying exploration of these definitions, which illuminates the terms used in this project. He defines the Gothic genre as texts that “will invoke the tyranny of the past . . . with such weight as to stifle the hopes of the present” (xix). These tyrannies are often authoritative and patriarchal institutions like Catholicism, American slavery, or colonialism. Baldick concludes that Gothic texts remain popular because of their ability to function as “a way of exercising such anxieties,” even though most of these institutions no longer have unmitigated authority (xxii). Baldick understands that the Gothic genre is a process or experience for the reader. His definition also points out a timelessness of the genre. Past horrors can trigger present ones, so the texts remain applicable to all readers. Since the 1970s when Ellen Moers conceptualized the Female Gothic as Gothic texts written by women, scholars have debated the range and validity of the subgenre and struggled with its problematic qualities. With the same concepts that produced New Wave Feminism, the Female Gothic of the 1970s can be re-explored and re-envisioned in order to be better understood in the current scholarly discussion. I alter the definition of the Female Gothic genre to be those Gothic texts that have a female protagonist threatened by patriarchy. This definition does appear broad, but it is not all-inclusive. It draws limitation from the elements of what makes up the Gothic genre and focuses on the patriarchal threat, instead of being limited by the application of the term “Female.” Building from Baldick’s definition, I explore Female Gothic texts as an experience of past patriarchal threat that invokes current social anxieties fomented by rape culture. The isolation that occurs in these texts via the geographical displacement and lack of community mirrors the isolation that women experience today that occurs because of the exclusion of women’s sexual experiences from public belief. In Ann Radcliffe’s The Italian (1797), there is the element of helplessness. In Matthew Lewis’s The Monk (1796), there is the element of horror. Then in Charlotte Bronte’s Jane Eyre (1847), there is the element of hope. I read these three novels as metaphorical representations of the helplessness, horror, and hope that typify reader’s fear of or experience with rape culture today. These elements manifest through the interaction of the female protagonists with the isolation and sexual threat. This interaction creates a shared experience for the reader.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts-English